Investigating the Influence of Halal Certification on Market Access and Business Growth for MSMEs in Indonesia - Azzahra, Asiyah; Andriansyah, Yuli; Hattabou, Anas (IAIN Manado, 2025)
This study investigates the impact of halal certification on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The purpose of the research is to assess both the benefits and challenges associated with halal certification for MSMEs, with particular attention to the barriers faced by smaller businesses. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with MSMEs owners. The findings reveal that halal certification significantly enhances market access, leading to increased sales, a broader customer base, and improved consumer trust. However, smaller MSMEs encounter substantial challenges, including high certification costs, bureaucratic complexities, and lack of awareness. Government programs, such as those offering subsidies and training, have proven beneficial in addressing some of these barriers, but there is still room for improvement. The study contributes to the existing literature by highlighting the specific barriers faced by smaller businesses and the importance of government support in overcoming these challenges. The implications suggest that streamlining the certification process, providing targeted financial assistance, and enhancing awareness programs are crucial for enabling more MSMEs to participate in the halal economy. The study calls for further research to explore the long-term impact of halal certification and the role of digitalization in simplifying the certification process.